IMPACT OF LEAN CONSTRUCTION IMPLEMENTATION ON CONSTRUCTION BUILDING PROJECTS - Abdhy Gazali; Aldy Riza Dhiandra; Muhammad Sapto Nugroho; Alfandi Ziqri; Lintang Tirta Sari (LPPM Universitas Negeri Jakarta, 2025)
Enhancing efficiency, minimizing waste, and improving project productivity are key objectives in Lean Construction. This study explores the impact of Lean Construction implementation at PT PP by examining the correlation between Planned Percentage Complete (PPC) in the Last Planner System (LPS) and project performance, including productivity and cost efficiency. The research employs a descriptive statistical analysis method, with data collected through a self-assessment survey and an evaluation of the correlation between PPC and key project management factors. The results indicate that LPS implementation significantly enhances productivity, with a positive correlation between PPC values and project efficiency. Furthermore, waste analysis reveals that Waiting, Defect, and Overproduction are construction projects' most dominant waste categories. This study also identifies that Lookahead Planning within LPS is crucial in reducing constraints, positively impacting project timeliness and cost control. Consequently, the findings provide deeper insights into Lean Construction implementation and offer strategic recommendations for companies to sustainably enhance efficiency and project performance.